A high-throughput synthesis of large-sized single-crystal hexagonal boron nitride on a Cu–Ni gradient enclosure. Issue 27 (23rd April 2020) - Zhu, Tianyu; Liang, Yao; Zhang, Chitengfei; Wang, Zegao; Dong, Mingdong; Wang, Chuanbin; Yang, Meijun; Goto, Takashi; Tu, Rong; Zhang, Song
Abstract : Large monolayer two-dimensional h-BN can be employed in novel electronic devices because of its thin insulation, excellent thermal stability, and high mechanical strength. Abstract : Large monolayer two-dimensional h-BN can be employed in novel electronic devices because of its thin insulation, excellent thermal stability, and high mechanical strength. However, the efficient synthesis of an h-BN film with large lateral size still faces a great challenge. Here, we report a method for the high-throughput synthesis of large-sized single-crystal h-BN on a Cu–Ni gradient alloy enclosure as the substrate via a low-pressure chemical vapor deposition (LPCVD) method. By depositing Ni on the Cu foil in different concentrations to obtain a Cu–Ni in-plane gradient concentration alloy enclosure, the highest growth rate of h-BN was 1 μm min −1 with the lateral size of h-BN being higher than 60 μm. Furthermore, the effect of the Ni content on the single crystal h-BN grain size and nucleation density and the mechanisms for the growth of h-BN were also investigated.